2021
DOI: 10.1155/2021/1822776
|View full text |Cite|
|
Sign up to set email alerts
|

Computer-Aided Diagnosis of Children with Cerebral Palsy under Deep Learning Convolutional Neural Network Image Segmentation Model Combined with Three-Dimensional Cranial Magnetic Resonance Imaging

Abstract: In this paper, we analyzed the application value and effect of deep learn-based image segmentation model of convolutional neural network (CNN) algorithm combined with 3D brain magnetic resonance imaging (MRI) in diagnosis of cerebral palsy in children. 3D brain model was segmented based on CNN algorithm to obtain the segmented MRI images of brain tissue, and the validity was verified. Then, 70 children with cerebral palsy were rolled into the observation group (n = 35), which received MRI for diagnosis after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…In another study, early diagnosis of cerebral palsy among very-preterm infants involved utilization of sensorimotor-tract biomarkers in assessing for any presence of brain damage among these infants [ 27 ]. One study uncovered increased accuracy in the detection of cerebral palsy from MRI imaging of segmented brain tissue based on the 3D model of a convolutional neural network [ 28 ]. A different study revealed that fractional anisotropy in the corticospinal tract at the internal capsule level yielded efficacy in identifying infants with periventricular white-matter injury as having or not having spastic cerebral palsy [ 29 ].…”
Section: Prevalent Typologies Of Diagnostic Imaging For Cerebral Palsymentioning
confidence: 99%
“…In another study, early diagnosis of cerebral palsy among very-preterm infants involved utilization of sensorimotor-tract biomarkers in assessing for any presence of brain damage among these infants [ 27 ]. One study uncovered increased accuracy in the detection of cerebral palsy from MRI imaging of segmented brain tissue based on the 3D model of a convolutional neural network [ 28 ]. A different study revealed that fractional anisotropy in the corticospinal tract at the internal capsule level yielded efficacy in identifying infants with periventricular white-matter injury as having or not having spastic cerebral palsy [ 29 ].…”
Section: Prevalent Typologies Of Diagnostic Imaging For Cerebral Palsymentioning
confidence: 99%
“…CNN, also termed feed-forward neural networks, are used for classification, image processing and pattern recognition. They are also used for detection of Seizures [19],with 96.05% accuracy, Cerebral Palsy [20], with 88.6%, Parkinson's [21], with 96.5%, and Alzheimer's [22]with 78.02% accuracy. Figure 3…”
Section: Cnnmentioning
confidence: 99%
“…But, the manual annotations take a long time and it needs more video frames to solve overfitting during training. A deep CNN-based image segmentation framework [22] was integrated with 3D cranial magnetic resonance imaging for diagnosing children with CP. However, the number of samples was insufficient to achieve the highest efficiency.…”
Section: Literature Surveymentioning
confidence: 99%